2021
DOI: 10.1103/physrevapplied.16.024058
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Generation via Picosecond Spin-to-Charge Conversion in IrMn3/NiFe Heterojunction

Abstract: † Cheng Li, Bin Fang and Like Zhang contributed equally to this work. nanoseconds, which cannot support applications in the ter-44 ahertz field. To tackle this issue, the approach of applying 45 a femtosecond laser pulse in a specifically designed mag-46 netic heterostructure [18] is proposed, which reduces the 47 timescale of spin-electricity conversion to the subpicosec-48 ond range, enabling the engineering of terahertz spintronic 49 devices. Therefore, this holds out the promise of spin-50 tronic terahertz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The trend of THz amplitudes with respect to NM materials is in good agreement with the calculated spin-Hall conductivity. Related works [52][53][54][55][56] also studied NM materials, such as Au, Ru, Al, IrMn 3 , and Mn 2 Au. At present, Pt is still the best choice for preparing NM layers, owing to the lesser effect on the THz amplitude for STEs.…”
Section: Optimizing Materialsmentioning
confidence: 99%
“…The trend of THz amplitudes with respect to NM materials is in good agreement with the calculated spin-Hall conductivity. Related works [52][53][54][55][56] also studied NM materials, such as Au, Ru, Al, IrMn 3 , and Mn 2 Au. At present, Pt is still the best choice for preparing NM layers, owing to the lesser effect on the THz amplitude for STEs.…”
Section: Optimizing Materialsmentioning
confidence: 99%
“…More Recently, it has been shown Mn 2 Au can be coupled ferromagnetically at the interface to Permalloy with one-to-one imprinting of the AFM order on the FM domains 10 , though little is known of the switching dynamics and whether one can simultaneously take advantage of the higher frequency dynamics of the AFM whilst being coupled to the sluggish FM. While AFM/FM bilayer systems have remained largely unexplored for reversal applications, Efforts have already been made to develop and understand the use of FM/AFM bilayers as THz emittors 23 25 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that Mn 3 Sn and Mn 3 Ir can be unutilized to construct THz emitters. [114,115] In addition, the large AHE signals have been shown to survive at a THz frequency at room temperature, which is beneficial for THz information reading (Fig. 5).…”
mentioning
confidence: 99%